Effects of cryotherapy on function, pain intensity, swelling, and dorsiflexion range of motion in acute ankle sprain: Protocol for the FROST randomised controlled trial - Julio Miranda; Hytalo Jesus Silva; Fabiane Gontijo Correa; Rafaela Figueiredo; Gabriel Fonseca; Victor Guilherme Oliveira; Sérgio Samuel Borba Fonseca Silva; Samuel Pereira Santos; Itayano Mendes Lamas; Frederico Ataíde; Anderson Santons; Sérgio Antunes Santos; et al. (PLoS ONE, 2025)
Background Cryotherapy is a low-cost treatment option recommended by clinical practice guidelines in acute ankle sprain. However, the current quality of the evidence that supports cryotherapy is still unclear. New high-quality randomised controlled trials are needed. The aim of the Freeze On Sprain Trial (FROST) is to investigate the effectiveness of cryotherapy on function, pain intensity, swelling and dorsiflexion range of motion in people with an acute episode of ankle sprain. Methods This is a protocol of a two-arm randomised controlled trial. Eighty-two participants over 18 years old presenting grade I or II ankle sprain up to 72 hours from the episode will be randomly allocated to Ice Group (i.e., home prescription to apply cryotherapy on the injured ankle with elevation plus non-steroidal anti-inflammatory medication – NSAID) or No Ice Group (i.e., elevation plus NSAID). Our primary outcome is function measured by the Lower Extremity Functional Scale (LEFS) questionnaire. Our secondary outcomes are pain intensity (11-point numerical rating scale), swelling (figure-of-eight method) and dorsiflexion range of motion (goniometry). Participants will be assessed at baseline, 24 hours, 7–10 days, and 12 weeks after allocation. The analysis will follow the intention-to-treat principle using linear mixed models. Discussion The results of this study will clarify the effectiveness of cryotherapy in acute ankle sprain for better clinical decision-making processes. Trial registration Brazilian Clinical Trials Registry (REBEC) RBR-8v9gr9c.